2020
DOI: 10.7150/jca.38796
|View full text |Cite
|
Sign up to set email alerts
|

A Combined four-mRNA Signature Associated with Lymphatic Metastasis for Prognosis of Colorectal Cancer

Abstract: Background: Colorectal cancer (CRC) is one of the most common malignant tumors in the world. Lymph node metastasis (LNM) is a common mode of metastasis of CRC. However, the combined mRNA biomarkers associated with LNM of CRC that can effectively predict CRC prognosis have not been reported yet. Methods: To identify biomarkers that are associated with LNM, we collected data from the The Cancer Genome Atlas (TCGA) database. The edgeR package was searched to seek LNM-related genes by comparisons between cancer sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…As a result, the AUC was, respectively, 0.653 and 0.74 for COAD and READ, which were both lower than that of our signature panel. Moreover, in line with other signature panels identified for CRC or CC patients [ 6 9 , 24 ], our risk score was demonstrated to be an independent factor for the prognosis prediction and stratify the survival of patients with the same TNM stage. Also, the AUC and the C-index of the risk score were higher than those of age (AUC = 0.5; C-index = 0.569), pathologic M (AUC = 0.503; C-index = 0.555), pathologic N (AUC = 0.672; C-index = 0.658), and pathologic stage (AUC = 0.549; C-index = 0.610) and the model with all clinical factors (AUC = 0.843; C-index = 0.817).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…As a result, the AUC was, respectively, 0.653 and 0.74 for COAD and READ, which were both lower than that of our signature panel. Moreover, in line with other signature panels identified for CRC or CC patients [ 6 9 , 24 ], our risk score was demonstrated to be an independent factor for the prognosis prediction and stratify the survival of patients with the same TNM stage. Also, the AUC and the C-index of the risk score were higher than those of age (AUC = 0.5; C-index = 0.569), pathologic M (AUC = 0.503; C-index = 0.555), pathologic N (AUC = 0.672; C-index = 0.658), and pathologic stage (AUC = 0.549; C-index = 0.610) and the model with all clinical factors (AUC = 0.843; C-index = 0.817).…”
Section: Discussionsupporting
confidence: 83%
“…Although all of the 5 signature genes were not included in the previous signature panels for CRC [ 6 9 , 24 ], some of them were found to be associated with the progression and prognosis of CRC (including ASB2, GPR15, TCL1A, and PRPH) [ 28 31 ]. High ASB2 expression was shown to predict a short relapse-free survival for patients with CRC [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, more and more multiple-biomarker signatures and prognostic nomograms have been established and utilized for clinical decision-making and prognostic evaluation for different type of cancers (5,(10)(11)(12). However, few biomarker-based signatures and prognostic nomograms have been studied in relationship to OTSCC (13)(14)(15).…”
Section: Discussionmentioning
confidence: 99%
“…Proliferation, migration, and invasion of gastric cancer cells are associated with EPHA8 kinase-mediated signaling involving the ADAM10 protein and downstream serine/threonine kinase AKT pathways [ 180 ]. Increased EPHA8 expression also associates with increased clinicopathological features or poor prognoses in oral tongue squamous cell carcinoma [ 181 ], colorectal cancer [ 182 ], and ovarian cancer [ 183 ]. Studies of EPHA8 phosphorylation sites revealed physical associations between EPHA8 and FYN proto-oncogene kinase (FYN) and implicate FYN kinase as a major downstream target for EPHA8 signaling [ 184 ].…”
Section: Ephrin Receptor A8 Kinase (Epha8)mentioning
confidence: 99%